Some aspects of privatization effects on the labor market in the Republic of Serb - Zimonjić Stefan (Trendovi u Poslovanju)
In the last more than 30 years transformation of numerous state-owned companies has been privatized in countries that started the transition process from socialism to free trade and capitalism including Serbia. Many economic studies prior to the transition process have started pointing out the importance of these changes for economic development and efficient growth of economies. After these processes were established, many praised privatization and its positive impact on economies on the whole as well as on micro levels of the firms. Regardless of studies and their findings, the interesting part is the public opinion of those processes which is generally very suspicious in terms of their benefits. It is not hard to understand the reasons, privatization is hard to sell in political and social terms, it leads to many unpopular decisions and impacts on the working class, it brings changes that are sometimes hard to understand and accept, as positive, people that are perceived as unproductive, lose their jobs and stay without income in very volatile external conditions. Privatization result is positively perceived in transition countries but in Serbia dominant perception is that it has been badly realized and has had a big and negative impact on labor and layoffs. The conclusion is that privatization has led to a worse set of selected models, as well as problems in the implementation and problems of annulment of one of their important parts.